IMPLICATION OF SUPERVISION OF VILLAGE REGULATIONS IN THE CONCEPTION OF VILLAGE AUTONOMY BASED ON LOCAL WISDOM REVIEWING FROM LAW NUMBER 6 YEAR 2014 ON VILLAGE - Nur Jihan; Firdaus Firdaus; Fatkhul Mu'in (JHR (Jurnal Hukum Replik), 2022)
Village regulations are a product of village law which comprises material for administering village government based on the original autonomy of the village. The mechanism for annulling or examination village regulations due to preventive and repressive supervisory functions by the Regional Government can reduce the village government in regulating and managing its own household. There are two identifications raised in this study, firstly how are the form of supervision of village regulations according to Law Number 6 of 2014 on Villages, secondly what are the implications of local government supervision of village regulations in the perspective of village autonomy according to Law Number 6 of 2014 on Villages. In order to answer the problem identification mention above, the method used is descriptive analytical with normative juridical and empirical juridical approaches from the types of data, both primary data and secondary data. With primary legal materials, secondary legal materials, and tertiary legal materials analyzed juridically qualitatively.keywords: village regulations, village autonomy, supervision